Importance of triple tumor markers as biomarkers in patients with pancreatic ductal adenocarcinoma. Issue 2 (11th October 2022) - Takagi, Tadataka; Nagai, Minako; Nishiwada, Satoshi; Terai, Taichi; Yasuda, Satoshi; Matsuo, Yasuko; Doi, Shunsuke; Kohara, Yuichiro; Sho, Masayuki
Abstract: Aim: There is an urgent need to establish biomarkers for the treatment of pancreatic ductal adenocarcinoma (PDAC). The aim of this study was to investigate the usefulness of the combined assessment of carbohydrate antigen 19‐9 (CA19‐9), carcinoembryonic antigen (CEA), and duke pancreatic monoclonal antigen type 2 (DUPAN‐2) in PDAC. Methods: We retrospectively investigated the impact of three tumor markers on overall survival (OS) and recurrence‐free survival (RFS). Patients were classified into two groups: upfront surgery (US) and neoadjuvant chemoradiation (NACRT) groups. Results: In total, 310 patients were evaluated. In the US group, patients who had all three elevated markers showed a significantly worse prognosis than the others (median: 16.4 months, P = .005). In the NACRT group, patients who had elevated CA 19‐9 and CEA levels after NACRT had significantly worse prognosis than the others (median: 26.2 months, P < .001). The elevated DUPAN‐2 levels before NACRT were associated with significantly worse prognosis than normal levels (median: 44.0 vs 59.2 months, P = .030). Patients who had elevated DUPAN‐2 levels before NACRT with elevated CA 19‐9 and CEA levels after NACRT showed extremely poor RFS (median: 5.9 months). Multivariate analysis revealed that a modified triple‐positive tumor marker indicating elevated DUPAN‐2 levels before NACRT and elevated CA19‐9 and CEA levels after NACRT was an independent prognostic factor of OS (hazard ratio: 2.49, P = .007) and RFS (hazard ration: 2.47, P = .007). Conclusions: The combined evaluation of three tumor markers may provide useful information for the treatment of patients with PDAC. Abstract : In the upfront surgery group, patients who had all three elevated tumor markers including CA19‐9, CEA, and DUPAN‐2 showed a significantly worst prognosis. In the neoadjuvant chemoradiation group, patients who had elevated DUPAN‐2 levels before NACRT with elevated CA 19‐9 and CEA levels after NACRT showed extremely poor RFS. The combined evaluation of these three tumor markers may provide useful information for the treatment of patients with PDAC.